Seed source variation in growth and biomass attributes of Ulmus villosa under nursery conditions in Punjab - Saralch, Harmeet Singh; Sodhi, Rishabh; Thakur, Sapna; Kumari, Anita (Indian Journal of Agroforestry, 2023)
The present investigation aims to reflect the extent of genetic variability existing among seed sources of Ulmus villosa for growth and biomass traits and selection of best seed source for Punjab conditions. Seeds were collected from five different seed sources distributed in the districts of Kullu, Mandi and Solan in Himachal Pradesh and were subjected to similar growth and environmental conditions in the nursery. Significant variations were observed among seed sources for all the growth and biomass characteristics. On the basis of mean performance, S5 (Nauni, district Solan) and seed source S1 (Suket, district Mandi) outperformed rest of the seed sources for all the growth and biomass characteristics and were selected for further field evaluation. High heritability and genetic gain was observed in root fresh weight (76.92%, 45.69%). Highly significant positive genotypic and phenotypic correlations were observed for most of the traits. Principal component analysis revealed that shoot fresh weight, along with other traits (shoot dry weight and collar diameter), were the largest contributors towards total genetic diversity in the progenies. Hence, maximum weightage should be attributed to shoot fresh weight, shoot dry weight and collar diameter while performing selection for the improvement of the species.